Advances in 2D magnetic chromium tellurides: synthesis, characterization, and spintronic applications - Zhang, Xiaoqian; Li, Peng; Bian, Guang (Reports on progress in physics, 2025)
Two-dimensional (2D) magnetic materials exhibit a wide array of fascinating magnetic properties, making them highly attractive for spintronic applications such as high-density nonvolatile memories and multifunctional nano-devices. Recently, chromium tellurides (CrTe ) have attracted significant attention due to their metallic band structure, strong magnetic anisotropy, and tunable exchange couplings. The unique tunability of magnetic properties in a metallic ground state makes CrTe a promising platform for generating, controlling, and manipulating spin currents. This review summarizes recent advances in large-scale 2D magnetic CrTe epitaxial thin films, emphasizing synthesis techniques that produce high-quality, large-area films. It explores the role of self-intercalation and heterostructure engineering in tailoring the magnetic and structural properties of these materials. We also review the band structure, magnetic characteristics, and spin dynamics of CrTe , with a particular emphasis on thickness-dependent band dispersion, magnetic anisotropy, and the emergence of skyrmions. Moreover, this review highlights the applications of CrTe in spintronics, covering the anomalous Hall effect, topological Hall effect, spin valves, and spin-orbit torque devices. The goal of this review is to furnish readers with a comprehensive overview of the intriguing properties of CrTe compounds and to inspire further innovative studies on the vast potential of 2D magnetic materials for next-generation spintronic and quantum devices.